Differential analysis of executive functions in children from disadvantaged families vs. children with autistic spectrum disorder - Gómez-Pérez, María del Mar; Calero, M. Dolores (Anales de Psicología / Annals of Psychology, 2020)
Executive Functions (EF) are considered necessary for dealing with new situations and for controlling one’s behavior. Studies have confirmed EF difficulties in children with autism spectrum disorder (ASD) and in children from disadvantaged families (DF). This study aimed to examine EF difficulties in the two populations –ASD and DF children- with respect to EF in children who show typical development (TD). A total of 89 children between the ages of 7 and 12 years participated, divided into three groups: 28 with ASD, 36 from DF and 25 with TD. Assessments were made with different measures of EF (executive attention, cognitive flexibility, inhibition and working memory) and central coherence. In general, the children from DF obtained the lowest scores in all measures, although differences were not significant with respect to the other groups in all cases. Children with ASD obtained similar scores to the TD group in executive attention and working memory, and higher scores in central coherence. In comparison to the children from DF, the ASD children did better on all measures. These results would indicate that intervention programs designed for the two groups must be focus on different kind of tasks.